An analysis of the factors that influence voting behavior in Zimbabwe: the case of Zvishavane district - Satiya, Omar N. (Midlands State University, 2018)
Zimbabwe’s economy is nose diving, deteriorating living standards, sky rocketing inflation, unemployment to mention but a few and electorates make their choices based on the policy and economic preferences. Despite these prevailing uncertainties with regards to Zimbabweans, the government and state has been under the guardianship of ZANU PF since independence in 1980. Therefore, this research seeks to investigate and analyze on the factors that influence voter behavior, as this has implications towards the outcomes of the elections in Zimbabwe. The researcher also took the liberty of looking at the recommendations to government, other political and academics. The study made use of a descriptive research design in which various instruments were used to gather data in the form of Interviews, questionnaires and observations. Using descriptive statistics, the outcome of the research highlighted that various factors influence voting behavior in Zvishavane which is the case study and these factors includes economic issues, party message or policies, candidates’ personality, party identification or affiliation to mention but a few. Ethical considerations were observed to preserve the integrity and authenticity of the study. The study also looked at the nature of elections in Zimbabwe which has been described as not free and fair and characterized with various mechanism of electoral fraud. Therefore, the research findings led to the conclusion that indeed there are various genuine factors that influence voting behavior, but the stay of Zanu Pf on power was due to electoral fraud at most. In this regard, the researcher recommends that the government must take concrete steps towards creating an environment for credible elections engaging with all relevant stakeholders and come up with actionable areas for the election roadmap with voters’ behavior being at the epicenter of the election outcomes.